(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: Migration is one of the socioeconomic factors that contribute to the acquisition and dissemination of sexually transmitted disease/s (STDs), a long-recognized major global health issue. This study aimed to determine the seroprevalence of STDs among Nepalese overseas job seekers. Methods: Retrospective serological data of Nepalese overseas job seekers (n=14,980), who were tested for Hepatitis B (HB), Hepatitis C (HC) and Acquired Immune Deficiency Syndrome (AIDS) with an enzyme-linked immunosorbent assay, and syphilis with Treponema pallidum hemagglutination assay, were extracted (January and December 2021) from the electronic database of a diagnostic center and analyzed using SPSS version 17.0. Results: Syphilis seroprevalence was 0.59% among overseas job seekers, while HB, AIDS, and HC seroprevalences were 0.32%, 0.15%, and 0.11%, respectively. Unlike syphilis, which was predominated in the age group of 31-40 years, viral hepatitis and AIDS were prevalent in the age group of 21-30 years. Males had higher incidences of HB (n=48), HC (n=17), AIDS (n=23), and syphilis (n=86) compared with females. Co-prevalence of HIV-syphilis and HIV-HBV occurred in 0.020% (n=3) and 0.013% (n=2) of individuals, respectively, whereas both HIV-HCV and HBV-HCV co-prevalence was observed in 0.007% (n=1) of individuals. Conclusion: Syphilis is the most common STD among Nepalese overseas job seekers, with the highest co-occurrence with AIDS.